Salinan Akta Perjanjian dalam Kredit Perbankan - Sopamena, Ronald Fadly (Bacarita Law Journal, 2022)
After an agreement is reached and the agreement is signed, the bank sometimes does not provide a copy of the credit agreement deed to the debtor. This will cause the debtor to find it difficult to remember the contents of the credit agreement in the future so that the debtor directly will also find it difficult to remember his rights and obligations. Thus, this study will examine the copy of the deed of agreement that is not submitted to the debtor. The research method used in this research is normative juridical or what is known as legal research which is carried out by reviewing and analyzing the substance of legislation on the subject matter or legal issue in its consistency with existing legal principles. In contrast to financial institutions, banks do not have an obligation to submit a copy of the credit deed to the debtor so that the debtor cannot keep the copy for verification purposes and also access to obtain or reread information about the products and/services listed in the agreement deed is no longer available. accessed. So, the debtor should take the initiative to ask the bank to make a copy of the agreement deed because the position of the parties in the agreement is equal and balanced.